Autonomy and Control when Working with Humans—A Reflection on Sociotechnical Concepts - Amble, Nina (Nordic Journal of Working Life Studies, 2013)
The sociotechnical concepts of responsible autonomy and to be in control were originally developed from men’s work in order to describe and develop mostly industrial work. This article explores how these conceptions may be useful in modern service work, when working with humans. It is based on a set of development projects in mainly municipal care institutions in Norway, between 2000 and 2011. The projects were theoretically grounded in the Norwegian and international sociotechnical system theory (STS) tradition. It argues that there are many valuable lessons to be learnt from this tradition also concerning nursing and care work in the municipalities. However, the article points to a need for development of the concept control as autonomy to embrace “working with humans.” A central finding is that assistance and support from and to colleagues are prerequisites for “being in control.” Moreover, that development of trust through communication alongside work is necessary in order to establish relations of mutual support. Trust and mutual support point to the social relations at work; so in this way it takes the concept control as autonomy from an individual to a more collective concept as Trist et al. (1963) and Herbst (1974/1993) defined their concept of control as collective responsible autonomy. In a prospective perspective, the article sets up the hypothesis that an organization that combines the two, an individual together with a more collective scope on autonomy when working with humans, will meet what Kira (2006) calls as regenerative work. This means sustainability—in resources involved; health, quality, and milieu—through the staff ’s dominion over the conditions of their work.